0225 Cancer, mortality and acute myocardial infarction in workers exposed to respirable crystalline silica dust at a Swedish porcelain factory. (23rd June 2014) - Wiebert, Pernilla; Alderling, Magnus; Svartengren, Magnus; Gustavsson, Per; Plato, Nils
Abstract : Objectives: Exposure to silica dust is a health hazard in the ceramic industry. We studied cancer, mortality and acute myocardial infarction (AMI) among workers at a Swedish porcelain factory. Method: Annual average of exposure levels were estimated from 436 personal measurements of respirable crystalline silica dust (RCS) from 1971–2006. We investigated mortality, incidence of cancer, and first time event of AMI in men and women employed for at least one year at the factory in 1958–2009. We also studied the effect of latency, duration and cumulative exposure. Results: RCS-levels among highly exposed workers were five times higher than the OEL and ten times higher in the early 1970s as in 2000. We found a non-significant elevated risk for lung cancer, (SIR 1.39; 95 % CI 0.79–2.25) and a significant elevated risk of squamous cell carcinoma in men (SIR 2.37; 1.02–4.66). Mortality from respiratory diseases was increased (SMR 1.75; 1.22–2.44), especially in men (SMR 1.86; 1.22–2.70). Among women, the risk for mortality from diseases of the circulatory system and incidence of AMI was elevated but not statistically significant. We found no dose-response relationship. There were eight cases of silicosis, and seven appeared with more than 30 years latency. Conclusions: The increased risk for lung cancer and mortality from respiratory diseases was expected in view of the well-documented harmful effects of RCS. The tendency among women for increased mortality from diseases of the circulatory system and an increase in the incidence of AMI should be investigated in further studies.